ANALYSIS OF NATIVE AND ALKALI-TREATED AGAR FROM SPECIES OF Gracilaria (GRACILARIACEAE, RHODOPHYTA) COLLECTED FROM MORIB, MALAYSIA. - Chung, Kar-Mun; Soo, Sze-Sze; Teo, Swee-Sen; Phang, Siew-Moi (Malaysian Journal of Science, 2011)
Seaweeds are marine algae commonly found in brackish water to marine environments. The red seaweed Gracilaria (Gracilariaceae, Rhodophyta) is commonly exploited for the production of agar. Alkaline pre-treatment has been shown to increase the quality of agar in previous studies. The aim of this study was to compare the effect of native ( untreated) and alkali treatment on the yield and physical properties of agar from Gracilaria changii (Xia & Abbott) Abbott, Zhang & Xia, Gracilaria salicornia (C.Agardh) Dawson and Gracilaria edulis (Gmelin) Silva collected from Morib in Malaysia. Compared to native samples (control), an addition of alkali pre-treatment step which involved soaking samples with 0.5M NaOH for 1 hour at room temperature prior to extraction was included for the treated samples. Comparative analysis showed that alkali-treated agar of G. edulis gave the highest agar yield (82.56 %) whereas the highest gel strength was obtained from native agar of G. salicornia (430 ± 17.32 g cm-2). Alkali treatment was found to be effective only for the increase of gel strength in G. edulis but not in G. changii and G. salicornia. The native and alkali-treated agars in all species gave comparable gelling and melting temperature which were in the range of (36-39ºC) and (80-87ºC) respectively. The overall results showed that G. salicornia had superior agar quality and is thus a potentially good source for industrial use. Analysis on chemical properties of agars can be performed in future to determine the agar composition of these species.